Haptics-Augmented High School Physics Tutorials - Williams II, Robert L.; Chen, Meng-Yun; Seaton, Jeffrey M. (International Journal of Virtual Reality, 2001)
This article describes a unique project using commercial haptic interfaces to augment the teaching of high school physics. Since force is central to the teaching of physics, we believe that the use of haptics in virtual reality physics simulations has the potential for deeper, more engaging learning. Software has been developed which is freely-available on the internet, and HTML tutorials have been developed to support these haptics-augmented software activities in the teaching and learning of high school physics. Pilot study results are reported, which yielded positive feedback and suggestions for project improvement from high school physics students and teachers.